2020
DOI: 10.3390/biomedicines8110460
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Adaptation by Na+-Dependent Transporters and ACE2: Correlation with Hemostatic Crisis in COVID-19

Abstract: COVID-19 symptoms, including hypokalemia, hypoalbuminemia, ageusia, neurological dysfunctions, D-dimer production, and multi-organ microthrombosis reach beyond effects attributed to impaired angiotensin-converting enzyme 2 (ACE2) signaling and elevated concentrations of angiotensin II (Ang II). Although both SARS-CoV (Severe Acute Respiratory Syndrome Coronavirus) and SARS-CoV-2 utilize ACE2 for host entry, distinct COVID-19 pathogenesis coincides with the acquisition of a new sequence, which is homologous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 200 publications
(368 reference statements)
0
12
0
Order By: Relevance
“…It is considered an early event in the pathophysiology of CV disease, contributing to subclinical target organ damage [ 25 , 26 ]. Biomarkers and potential treatment strategies for thrombotic events remain under investigation [ 27 , 28 , 29 , 30 ]. In 1992, Celermajer et al reported the first non-invasive endothelial function test [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered an early event in the pathophysiology of CV disease, contributing to subclinical target organ damage [ 25 , 26 ]. Biomarkers and potential treatment strategies for thrombotic events remain under investigation [ 27 , 28 , 29 , 30 ]. In 1992, Celermajer et al reported the first non-invasive endothelial function test [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for MV measurements were collected in citrated tubes (sodium citrate 3.2%) and centrifuged within 30 min with a two-step centrifugation protocol (2500× g for 15 min at room temperature, followed by a second centrifugation of the supernatant at the same condition). Supernatant was collected, and platelet poor plasma was stored at −80 °C [ 29 ]. MVs detection was then performed on thawed samples using a CyFlow Cube8 ROBBY flow cytometer (Sysmex Partec GmbH, Goerlitz, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The ACE2 enzyme then converts AngII into the metabolite Ang-(1–7), which acts as a ligand for the Mas receptor (MasR). The MAS receptor elicits signalling opposing Ang II/AT1R effects, including the inflammatory ones, and inhibiting AT1R expression [ 61 ]. Both ACE2 and MasR are present in human Leydig and Sertoli cells ( Figure 2 ).…”
Section: Sars-cov-2 Impact On the Male Reproductive Systemmentioning
confidence: 99%
“…For sHLH, it has been hypothesized that environmental factors may also trigger or exacerbate an aberrant innate and acquired immune response with massive cytokine synthesis in genetically susceptible individuals [ 144 ]. Alteration of the ACE2 enzyme activity has been indicated as an important trigger of the pathologies seen in COVID-19 patients [ 61 ]. Inactivation of the ACE2 complex leads to thrombosis in infected and noninfected tissues, aberrant sensory and neurological perception in COVID-19 patients and, most importantly, to necrosis in pulmonary, endothelial, and cardiac cells.…”
Section: Mechanism Of Damage Of Sars-cov-2mentioning
confidence: 99%
“…The over-activation of the ENaC plays a crucial role in urinary potassium loss and subsequently reduced serum potassium levels [ 18 ]. Interestingly, ENaC and ACE2 expression share similar distributions in the tissues, including renal tubules, urinary bladder, colon epithelium, lung airway, and alveoli [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%